P273 'Ketting' the kids to sleep – implementation of a paediatric procedural sedation guideline at a mixed emergency department. (June 2019) - Moriarty, Tadgh; Markey, Gerard; Tarar, Umar
Abstract : Introduction: Ketamine hails from a stormy past, falling in and out of favour among our anaesthetic colleagues. However, the most recent data shows it has a favourable safety profile with relatively few absolute contraindications. This, combined with its applicability to a diverse patient cohort makes it a suitable choice for paediatric procedural sedation. University Hospital Waterford, a mixed emergency department, implemented a ketamine sedation guideline for use in our paediatric population in 2018. 33 patients successfully underwent sedation throughout the year with no major adverse events. Aims: The primary objective of this protocol was to enhance patient (and parent) experience within the ED. Secondary aims were reduced quaternary hospital referrals and less in-patient bed days. In-direct outcomes would include less parental (work) absenteeism, cost saving for parents, reduced hospital crowding, and a cost saving to the hospital. Methods: An extensive literature review, incorporating current UK (RCEM), Australian (ACEM) and American (ACEP) guidelines (and recommendations) for paediatric sedation was undertaken. Ketamine was chosen as the sole agent of choice and a comprehensive guideline was constructed. This four page document incorporated patient selection, resource requirement, adverse event management and a parent advice leaflet. Sedation training was offered to APLS trained middle grade doctors, while induction level training was provided to house officer doctors highlighting patient selection and the 'proceduralist' role. Results: 33 Paediatric procedural sedation have occurred since implementation. This has resulted in a direct cost saving to parents of €1680 for admission avoidance at UHW. Furthermore a cost saving of at least €4489 was made by parents in preventing onward travel to Plastic surgery at Cork University Hospital. A post sedation survey of parents was carried out which revealed a high level of satisfaction of the sedation. One parent reported nightmares in their child that night, and one parent reported an episode of vomiting in the car journey home. All would opt for local ketamine sedation again if required. Conclusion: This successful implementation underscores the role of paediatric procedural sedation within a mixed ED. Positive parent feedback stresses the benefit of providing paediatric procedural sedation to a select cohort of suitable patients in reducing travel for quaternary hospital services, and less hospital bed days. Cost saving to parents, and local access to services bolsters a positive patient and parent experience